Pengaruh Earning Per Share, Total Assets Turnover, Pertumbuhan Penjualan dan Debt Equity Ratio Terhadap Harga Saham - Intan Pratiwi; Ayu Noviani Hanum; Nurcahyono Nurcahyono (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to examine the effect of earning per share, total assets turn over, sales growth and debt to equity ratio on stock prices in the Food Beverage Sub Sector on the Indonesia Stock Exchange for the 2015-2019 period. The number of Food and Baverages sub-sector companies listed on the IDX from 2015 to 2019 were 26 companies. Multiple linear regression analysis was used to test the research hypothesis. The results showed that Earning Per Share had a positive significant effect on stock prices, Total Assets Turnover had a negative insignificant effect on stock prices, Sales Growth had a negative insignificant effect on stock prices, Debt to Equity Ratio had a positive significant effect on stock prices and. Meanwhile, EPS DER gave a positive signal to the increase in stock prices in the market, but TATO Sales Growth could not directly contribute to the increase in stock prices.